CFD ANALYSIS OF ENHANCEMENT OF TURBULENT FLOW HEAT TRANSFER IN A HORIZONTAL CIRCULAR TUBE WITH DIFFERENT INSERTS - Al – Abbasi, Sajid Hussein Ali (European Scientific Journal, ESJ, 2014)
The present work includes the results of CFD analysis of enhancement of turbulent flow heat transfer in a horizontal circular tube with different shapes of inserts (disc, diamond and trapezoidal), with air as working fluid. The Reynolds number ranged from 6000 to 14000. It is observed that enhancement of heat transfer as compared to the conventional bare tube at the same mass flow rate was found to be a factor of 3 to 5 times, were as the friction factor rise was about a factor of 5 times for different tube inserts. Finally we compared results with theoretical values (DITTUS-BOELTER EQUATION) by using tool of package of ANSYS-FLUENT. Geometries for plain tube, and tube with different inserts is developed in ICEM CFD (3D) with fine meshing and exported to ANSYS-FLUENT, then suitable boundary conditions are applied to these models and solved energy, momentum and turbulence equations and results obtained are discussed.